The Influence of Storytelling on EFL Students Motivation in Speaking Practice in SMPN 03 Bengkulu Tengah - Sri Noprianti; Ali Akbarjono; Feny Martina (Yayasan Karinosseff Muda Indonesia, 2021)
Based on the explanation of the theory by Gardner the state is motivation comes from within a person as a driving force to achieve goals for more advanced change. This study aims to determine how enthusiastic student's Eighth grade in the SMPN 03 Bengkulu Tengah are in learning English, especially speaking English. Researchers used a quasi-experimental research method, namely a control group posttest only design which showed a significant difference between 74, 92%, and 61.96% of the experimental class in the control class. From this hypothesis, the researcher obtained a comparison of the experimental class in the treatment using the storytelling method of 4.34% and the control class with the narrative picture method of 3.58%. So the researcher can conclude that there is a significant difference between the two methods with or without the use of treatment compared to the motivation to learn English in class VIII students at SMPN 03 Bengkulu Tengah.